NEUROPHARMACOLOGICAL PROPERTIES OF ETHANOL EXTRACT OF Adenopus breviflorus (ROBERTY)FRUIT IN MICE (2014)
Adenopus breviflorus is a perennial climber used locally as an anti-convulsant, sedative and pain-killer in West Africa. Several studies have reported gastrointestinal, reproductive and anti-microbial effects of extracts of Adenopus breviflorus, but there is dearth of information on its neurological effect. This study was therefore designed to investigate effect of Ethanol Extract of Adenopus breviflorus (EEAB) on central nervous system in mice. Three hundred gram of air-dried Adenopus breviflorus fruits were cold macerated in 70% ethanol and concentrated using rotary evaporator. One hundred and ninety-two Swiss male albino mice (20-25 g) were divided into control (distilled water), EEAB-treated (62.5, 125, 250, 500, 1000, 2000 mg/kg, p.o.) and diazepam-treated (2.0 mg/kg) groups (8 per group) for neurobehavioural studies; fifty-six mice(20-25 g) (8 per group) were used to evaluate mechanisms of action using different antagonists (0.5 mg/kg atropine, 0.5 mg/kg cyproheptadine, 0.2 mg/kg haloperidol, 2.0 mg/kg naloxone, 0.2 mg/kg propranolol and 1.0 mg/kg yohimbine). Sixty-four mice (20-25 g) were divided into control and EEAB-treated groups (62.5, 125, 250, 500, 1000, 2000 mg/kg, p.o.) (8 per group) for Y-maize test. One hundred and sixty mice (20-25 g) (8 per group) were divided into control and EEAB-treated groups (250, 500, 1000, 2000 mg/kg, p.o.) for analgesic study; 32 mice (8 per group) were used to evaluate mechanism of action using naloxone (2 mg/kg). Neurobehavioural studies were carried out using novelty-induced rearing, grooming and locomotor activity in open-field. Head dips rate was determined using hole-board. Effect on memory was performed using Y-maze test. Analgesic activity was carried out using hot plate, tail immersion, formalin and acetic acid-induced writhing tests. Data were analysed using descriptive statistics and ANOVA at p=0.05. The EEAB (250-2000 mg/kg) significantly decreased rearing (86.6+2.1, 84.6+2.7, 62.8+2.4, 23.6+2.8, relative to control 131.2+2.9). Diazepam also significantly decreased rearing (11.0+2.6 relative to control 131.2+2.9). The EEAB (62.5-2000 mg/kg) significantly decreased grooming, locomotor activity and head dips relative to controls (32.8-8.0 versus 36.2+2.6, 77.8-29.8 versus 121.0+3.4 and 15.0-6.8 versus 32.6+1.8 respectively). Diazepam also significantly decreased grooming, locomotor activity and head dips relative to controls (14.4+1.7 versus 36.2+2.6, 49.6+1.3 versus 121.0+3.4 and 6.2+1.1 versus 32.6+1.8 respectively). Three antagonists (2 mg/kg naloxone, 0.2 mg/kg propranolol, 1.0 mg/kg yohimbine) reversed effect of EEAB (2000 mg/kg) on rearing relative to controls (112.4+2.9 versus 131.2+2.9, 113.8+2.8 versus 131.2+2.7 and 110.4+1.3 versus 131.2+2.7 respectively). The EEAB (62.5-2000 mg/kg) significantly increased memory (65.4+1.8, 66.0+2.9, 66.6+1.6, 68.4+2.3, 74.2+2.1, 77.6+2.9 relative to control 58.2+2.7). The EEAB (250-2000 mg/kg) significantly increased reaction time (min) to thermal stimulus of hot plate (2.2+0.2, 2.8+0.4, 2.80+0.4, 3.6+0.3 relative to control 1.0+0.0) and hot water (2.8+0.3, 2.8+0.3, 3.4+0.4, 20.0+0.1 relative to control 1.0+0.0). The EEAB (250-2000 mg/kg) also significantly reduced acetic acid-induced writhes (33.6+1.1, 15.8+1.1, 13.8+0.9, 4.0+0.5 relative to control 41.4+1.8) and decreased paw-licking time (sec) in formalin-induced neurogenic pain (44.0+2.6, 38.2+2.8, 27.6+2.8, 4.6+0.6 relative to control 76.0+3.7) which were all reversed by naloxone (2 mg/kg). Adenopus breviflorus had central nervous system depressant and analgesic effects which could be mediated via µ-receptor, β and α2- adrenergic receptors.